Formulation of Ginger (Zingiber Officinale)-Based Energy Drink Using Tea-Derived Caffeine: A Comparative Energy Analysis - SITI SYAZLIANA MD SAAD,; Nor Faizah Razali, (Progress in Engineering Application and Technology, 2026)
Energy drinks are one of the most consumed functional beverages among teenagers, athletes, and working adults. Commercial energy drinks are often associated with high sugar content and artificial additives that pose health concerns if consumed regularly. This paper aims to formulate a natural ginger-based energy drink enriched with caffeine extracted from green tea and black tea leaves as a healthier alternative. Caffeine was extracted using Soxhlet extraction and was incorporated into 250 mL of ginger juice. Black tea produced a higher caffeine yield (5.59%) compared to green tea (1.22%). Nutritional analysis showed that the GT1 formulation (70 mg caffeine) had the highest energy content (164.84 kcal), while all samples maintained low sugar levels (9.83 g/L). Protein, fat, and fibre contents were negligible due to the use of natural ginger juice. The findings demonstrate that ginger juice combined with naturally derived caffeine can produce a functional energy drink with lower sugar content and improved energy value. Further studies on shelf life and consumer acceptability are recommended.